Modular structured multilevel inverter as a three-phase shunt active power filter with unified constant frequency integration control - Ismaail, Ali Ibrahim (2007)
In recent years, the usage of power electronics equipments continues to increase, due to the increased usage of nonlinear loads and distributed power sources. These nonlinear loads generate harmonics and reactive currents, which lead to low power factor, low energy efficiency, low power capacity, and harmful disturbance to other appliances. These reactive currents will distort the voltage at the point of common coupling, reducing the quality of power delivered to other consumers on the network. Nowadays shunt active power filters (APFs), due to their flexibility and reliability are one of the most versatile and efficient solutions in the compensation of the load power factor and current harmonics. APFs provide only the harmonic and reactive power to cancel the one generated by the nonlinear loads or sources. This project presents a Modular Structured Multilevel Inverter (MSMI) as a three-phase shunt active power filter with Unified Constant Frequency Integration (UCI) control. Using MSMI APF with a unified constant-frequency integration controller, a unity power factor and low total harmonic distortion can be realized in all three phases. The proposed control approach employs one integrator with reset, along with several logic and linear components such as flip-flops, comparators, and clock. There are several important features of this implementation, it does not require three-phase load current and phase voltage sensing, also the nontrivial task of calculating harmonics and reactive current component is not required, and finally, it does not use any multipliers. These features make the proposed control approach simple, robust and reliable. The proposed three-phase MSMI APF with UCI control was simulated using MATLAB/Simulink. Simulation results have demonstrated a good suppression in harmonic distortion and improvement in the power factor of the power system.